CLINICAL AND SYSTEM-RELATED FACTORS CONTRIBUTING TO POOR OUTCOMES IN STEMI PATIENTS WITH EARLY VERSUS DELAYED PRESENTATION (Asian Journal of Medical Research and Health Sciences, 2026)
Background: Coronary artery disease (CAD) is the leading cause of mortality worldwide. ST-segment elevation myocardial infarction (STEMI) requires prompt management to improve patient outcomes. Early revascularization, either through fibrinolysis or percutaneous coronary intervention (PCI), reduces myocardial ischemic time and prevents complications. However, treatment delays are common, particularly in developing regions such as Pakistan, adversely affecting patient outcomes. Identifying the factors responsible for these delays is essential. Objective: To compare clinical outcomes between STEMI patients presenting within 2 hours of symptom onset and those presenting after 2 hours. Study Design: Prospective comparative study. Duration and Place of Study: This study was conducted at People’s University of Medical and Health Sciences Nawabshah from February 2025 to February 2026 Methodology: This prospective comparative study included 180 patients with confirmed ST-segment elevation myocardial infarction (STEMI), aged 18–65 years. Patients were enrolled through consecutive non-probability sampling after obtaining informed consent. They were divided into two groups based on time to presentation (≤2 hours vs >2 hours). Data regarding demographics, clinical characteristics, and causes of delay were collected. Statistical analysis was performed using SPSS version 25, with a p-value ≤0.05 considered statistically significant. Results: A total of 180 patients were included and equally divided into two groups. A significantly higher proportion of patients in the delayed presentation group belonged to a low socioeconomic status (Group A: 65.5% vs Group B: 20.0%). Complications were more frequent in the delayed group, including reinfarction (18.8%), in-hospital mortality (12.2%), acute heart failure (10%), and arrhythmias (12.2%). Conclusion: Delayed presentation in STEMI patients is associated with increased in-hospital mortality and a higher risk of complications. Early recognition and timely management are critical to improving outcomes.